Evaluative processes in self-critical individuals: The role of success and failure inductions. (October 2016) - Rahamim, Ofer; Garbi, Dror; Shahar, Golan; Meiran, Nachshon
Abstract: Relying on the two-factor model of personality development (e.g., Blatt & Blass, 1992 ) and evolutional psychology perspective on self-criticism (SC; e.g., P Gilbert & Irons, 2005), we examined the role of evaluative processes in SC by investigating SC individuals' reactions to achievement success and achievement failure. We hypothesized that inducing achievement success or failure would activate the SC schema, and that such activation would result in enhanced automatic operation of the individual's evaluative system. In two experiments, an experience of achievement success or failure was induced by means of a fabricated intelligence test (Exp. 1A), or by an event recall (Exp. 1B & Exp. 2). Automatic evaluative processes were evaluated by a tailored task switching paradigm. While, SC was associated with enhanced automatic negative evaluation following a failure induction, it was associated with enhanced automatic positive evaluation following recalled achievement success. To the best of our knowledge, the results are the first documentation of bias towards positive information in SC. We discuss these results in terms of a potential resilience facet within SC. Highlights: We examined the role of evaluative processes in self-criticism (SC). Enhanced automatic negative evaluation following a failure induction was found. Enhanced automatic positive evaluation following success induction was found. We discuss these results in terms of a potential resilience facet within SC.